Modelling and simulation of photosynthetic activities in C3 plants as affected by CO2. Issue 3 (1st June 2019) - Wang, Sheng; Tang, Hao; Xia, Qian; Jiang, Yongnian; Tan, Jinglu; Guo, Ya
Abstract : CO2 concentration ([CO2 ]) in a greenhouse may be a limiting factor for plant growth. Current greenhouse CO2 control strategy usually depends on expert experience, which may control [CO2 ] in a moderate range but cannot make it optimal due to lack of considering plant photochemistry reactions. A state‐space kinetic model structure covering major photosynthetic reactions as affected by CO2 is useful for [CO2 ] control strategy development in a greenhouse because modern control theories are usually based on state‐space models. In this work, a state‐space kinetic model structure for photosynthesis was built, which describes the major reaction cascades of photophosphorylation, Calvin cycle, and biophysical processes such as CO2 transport through the stomata under moderate [CO2 ] range without considering photorespiration. Simulations were performed with a large range of model parameters to demonstrate the effect of [CO2 ] on stable sugar production and the flexibilities of the developed model structure. The results clearly show whether increasing of CO2 will lead to more production of sugar or not in different scenarios. The model structure may be extended to cover other photosynthetic influence factors such as temperature by using the well‐known Arrhenius equation.